Lista preliminar de los mamíferos (Mammalia: Theria) del departamento de Nariño, Colombia - Héctor E. Ramírez-Chaves (Biota Colombiana, 2010)
To consolidate the available information on terrestrial and marine mammals of the department of Nariño, voucher specimens from national collections as well as records from international museum databases and the scientific literature were investigated. A checklist of 182 mammalian species is presented. Out of those, 24 species are considered as threatened under some category in Colombia. Our work reveals the need of new efforts to fill out the mammalian information gaps for this portion of the country.